Driver Destination Models - Krumm, John; Horvitz, Eric (11th International Conference on User Modeling (UM 2007), June 25-29, 2007, Corfu, Greece., 2007)
Predictive models of destinations represent an opportunity in the context of the increasing availability and sophistication of in-car driving aids. We present analyses of drivers’ destinations based on GPS data recorded from 180 volunteer subjects. We focus on the probability of observing drivers visit previously unobserved destinations given time of day and day of week, and the rate of decline of observing such new destinations with time. For the latter, we discover a statistically significant difference based on gender.